Preclinical immunogenicity and protective efficacy of a SARS-CoV-2 RBD-based vaccine produced with the thermophilic filamentous fungal expression system Thermothelomyces heterothallica C1 - Gonzalez-Hernandez, Mariana; Kaiser, Franziska Karola; Steffen, Imke; Ciurkiewicz, Malgorzata; van Amerongen, Geert; Tchelet, Ronen; Emalfarb, Mark; Saloheimo, Markku; Wiebe, Marilyn G.; Vitikainen, Marika; Albulescu, Irina C.; Bosch, Berend-Jan; et al. (Frontiers in Immunology, 2023)
Introduction The emergency use of vaccines has been the most efficient way to control the coronavirus disease 19 (COVID-19) pandemic. However, the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern has reduced the efficacy of currently used vaccines. The receptor-binding domain (RBD) of the SARS-CoV-2 spike (S) protein is the main target for virus neutralizing (VN) antibodies. Methods A SARS-CoV-2 RBD vaccine candidate was produced in the Thermothelomyces heterothallica (formerly, Myceliophthora thermophila) C1 protein expression system and coupled to a nanoparticle. Immunogenicity and efficacy of this vaccine candidate was tested using the Syrian golden hamster (Mesocricetus auratus) infection model. Results One dose of 10-μg RBD vaccine based on SARS-CoV-2 Wuhan strain, coupled to a nanoparticle in combination with aluminum hydroxide as adjuvant, efficiently induced VN antibodies and reduced viral load and lung damage upon SARS-CoV-2 challenge infection. The VN antibodies neutralized SARS-CoV-2 variants of concern: D614G, Alpha, Beta, Gamma, and Delta. Discussion Our results support the use of the Thermothelomyces heterothallica C1 protein expression system to produce recombinant vaccines against SARS-CoV-2 and other virus infections to help overcome limitations associated with the use of mammalian expression system.